The favorite and the taboo in memories concerning forced resettlement - Koval’-Fuchylo, Yryna (Literatura Ludowa. Journal of Folklore and Popular Culture, 2022)
The article is devoted to the analysis of the favorite (popular) and the taboo (rarely verbalized) themes and motives in memories concerning forced relocation from flood zones resulting from the construction of hydroelectric power plants in Ukraine. Common topics include the idealization of the forsaken place, stories about helping one another, the emphasis on the loss of home, land, community, graves and cemeteries, as well as descriptions of meetings of migrants from the same. Unpopular topics concern the resettlement achievements as well as the migrants’ priorities and new opportunities. The topic selection is influenced by the chosen strategy of self-presentation, the narrator’s personal experience, and current moods in society as well as in the local community. The assessment of resettlement also depends on the respondents age. That event appears to have been the most difficult for people who were middle-aged and older at the time, who were actually forced to demolish their houses and build new ones in a new place, and become accustomed to new conditions. In the stories of people who were children during the resettlement, the emphasis is somewhat shifted towards stories about meetings former villagers, reflections on the meaning of erecting hydroelectric power plants and the ensuing ecological aftermath. The material analyzed in the article constitutes oral recollections of forced migration, recorded during 2012–2019 in places of mass resettlement from flooded villages.